ChatGPT as a Conversational Agent in Chinese Language Learning for Spanish Speakers - Xiaoling, Wang (Sinología hispánica. China Studies Review, 2026)
Based on the recent emergence of artificial intelligence such as ChatGPT, this study aims to explore the utilization of this linguistic model in the domain of a second language, specifically Chinese. The objective is to propose novel ideas regarding Chinese language learning strategies within the Spanish-speaking context, with the aim of improving the effectiveness of non-immersive teaching through the incorporation of tools like ChatGPT. Special attention is given to the development of conversational skills and the analysis of ChatGPT’s role in communicating with Chinese language learners, evaluating its effectiveness, accuracy, and cultural relevance in communication. The results suggest that ChatGPT has the potential to enhance student motivation for communication, refine the accuracy of instructional content, and effectively address their knowledge requirements in a relatively unbiased manner, which will help to facilitate the amelioration of intercultural barriers.